Direct Q-value determination of the β- decay of 187Re - Filianin, Pavel; Lyu, Chunhai; Door, Menno; Blaum, Klaus; Huang, W. J.; Haverkort, Maurits W.; Indelicato, P.; Keitel, Christoph H.; Kromer, Kathrin; Lange, Daniel; Novikov, Y. N.; Rischka, A.; et al. (Physical review letters, 2021)
The cyclotron frequency ratio of 187Os29+ to 187Re29+ ions was measured with the Penning-trap mass spectrometer PENTATRAP. The achieved result of R=1.000 000 013 882(5) is to date the most precise such measurement performed on ions. Furthermore, the total binding-energy difference of the 29 missing electrons in Re and Os was calculated by relativistic multiconfiguration methods, yielding the value of ΔE=53.5(10) eV. Finally, using the achieved results, the mass difference between neutral 187Re and 187Os, i.e., the Q value of the β− decay of 187Re, is determined to be 2470.9(13) eV.
Im Titel sind "-" und "187" hochgestellt
Gesehen am 05.05.2022